Molecular analysis of HIF activation as a potential biomarker for adverse reaction to metal debris (ARMD) in tissue and blood samples. Issue 5 (27th September 2018) - Nyga, Agata; Hart, Alister; Tetley, Teresa D.
Abstract: We aimed to find a biomarker for patients with adverse reaction to metal debris (ARMD) due to a metal‐on‐metal (MoM) hip implant. First, we compared molecular markers of hypoxia‐inducible factor (HIF) pathway activation ( BNIP3, GLUT1, HO1, VEGF, and HIF1A ) and inflammatory response ( IL1B and COX2 ) in tissue from patients undergoing revision of MoM hip implant with tissue from patients undergoing primary hip replacement (PHR). Second, we compared blood levels of the above molecular markers and additional inflammatory markers: TNFA, IL18, CASPASE1, NFKB or IKB, and TLR1–4 mRNA in patients with non‐failed MoM hips. We report the presence of increased expression of HIF‐target genes in the periprosthetic tissue in MoM patients when compared to the PHR group. This suggests HIF pathway activation due to MoM debris and the potential of using HIF targets as a predictor of failure. Analysis of blood samples from nonoverlapping, nonfailed, MoM group showed significantly higher expression of COX2 mRNA and significant correlations between HIF1A and GLUT1 mRNA expressions, and between HIF1A mRNA and selection of inflammatory genes, including IL18, IKB, TLR1, and TLR4 . HIF pathway activation in the periprosthetic tissue biopsies of patients with hip replacements may represent the first biomarker to identify early ARMD. Further studies investigating blood biomarkers could also prove beneficial in detecting ARMD that could lead to an early intervention and improved patient outcome after hip revision surgery. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1352–1362, 2019.